Numerical Investigation of Unsteady Interaction between Rim Seal Flow and Upstream Vane (Xibei Gongye Daxue Xuebao, 2019)
To investigate unsteady interaction mechanism between the rim seal flow in turbine stator-rotor cavity and main flow, detailed unsteady numerical simulations of the flow field and unsteady characteristic of the vane were conducted under different rim seal mass flow rate. The results show the blockage effect resulting from the egress flow leads to the pressure to increase and static entropy to reduce on the latter half of suction side near the hub. From the case without a cavity to RI=1.7%, at 5% span, the maximum pressure coefficient increase on the suction side reaches 6%. Moreover, the blockage effect causes the velocity to decrease at vane exit. Furthermore, the rim seal flow results in the decrease in lateral pressure gradient, causing the strength of hub passage vortex and hub trailing shedding vortex to reduce. Without rim seal flow, the ingress flow contributes to decreasing unsteady fluctuation from the hub to 10% span. When there is rim seal flow, unsteady fluctuation continues to reduce due to coupling effects of the egress flow from the ingress and the egress flow form the cavity inlet.